Developing high-performance microfluidic paper-based analytical devices - Nguyen, Michael Paul, author; Henry, Charles S., advisor; Van Orden, Alan, committee member; Strauss, Steven H., committee member; Marchese, Anthony J., committee member (Colorado State University. Libraries, 2018)
Small-scale systems to manipulate fluids, also referred to as microfluidics, have proven effective at reducing analytical costs by increasing the portability of diagnostic devices. Microfluidic paper-based analytical devices (μPADs) have also proven to be cost-effective while remaining disposable, possessing the capacity to store reagents, and producing quantitative diagnostic results. These benefits have lead the field to increase exponentially since the seminal publication, with 63 review articles currently published on the subject. Most articles in the field focus on three topics: 1) new applications, 2) new methods of analysis with broad applicability, and 3) new ways to manipulate fluids in devices. A host of new analytes and clever architectures are being developed for a variety of applications, including environmental analysis and diagnostics. However, several critical obstacles remain for μPADs including improving detection limits, reducing analysis time, increasing selectivity, and increasing the range of measurable analytes. The work described in this dissertation presents three studies that address these issues. The first study examines simple factors to improve sample delivery through a cellulose channel that directly and significantly impact detection limits. Here I show how common μPAD designs lose roughly 50% of sample prior to quantification. This major challenge has been solved through geometry changes that led to a 94% increase in signal when compared to standard designs. While Ni(II) detection was used to study the system, the methods are translated to Mn(II) detection, antibiotic purity tests and determination of nitrite in saliva suggesting the broad applicability of the methods. The second study aimed at decreasing analysis time by utilizing multiple layers of paper in μPADs. I present the ability to tune speed, distance, and time at which the fluid travels with the formation of a microchannel between the layers. By increasing both the number of paper layers and the distance between them, the solution flux is dramatically increased in agreement with theoretical predictions. However, experimental flow rates deviate from predictions at large spacings. The detailed characterization and current understanding of the fast flow properties allow us to design assays that take seconds to complete instead of minutes along with improved analytical performance.Developing a selective test for Al(III) in food, mining and water samples is the goal of the last study. To address this need, a fluorescent ligand selective for Al(III) was synthesized and characterized on a μPAD for the first time. A distance-based μPAD for Al(III) exhibited a linear response from 2–55 ppm and a limit of detection of 2 ppm. This chemistry was also further developed with a radial uPAD that measures diameter of a color response as opposed to distance. Despite a smaller linear range with this radial device, the limit of detection is 0.9 ppm, which is below the concentration relevant to plant health. All three of these studies highlight improving the analytical performance of μPADs with carefully selected assays and deliberate device design.